Structural Magnetic and Electrical Properties Of La0.67ca0.33mn03 Perovskite Synthesized Via Conventional and Co-Precipitation Methods - Ahmed Ali Salama, Hazar Ali (2004)
The structural, magnetic and electrical properties of lanthanum manganites having a nominal composition of Lao67C~.33Mn0s3y nthesized via co-precipitation method (COP) following sintering treatments at temperature ranging between 1100°C and 1350°C are reported. XRD pattern showed the monophasic orthorhombic structure of the sample sintered within the above temperature range for a sintering period of 24 hours. The SEM micrographs showed that the grains are well grown and clear grain boundaries are observed. The grain size increased significantly form 1.7pm to 10.3pm as the sintering temperature increases and were well compacted. Large grains growth with layered features is observed in samples sintered at higher temperature. Ferromagneticparamagnetic phase transition were observed in the f-temperature curves for all the sintered samples. The Curie temperature, T, shifts to lower temperature as the sintering temperature, Ts increases. All the samples show the typical ferromagnetic-paramagnetic phase transition, Tc in the range 267.9 K-259.7 K. The transport properties show the transition of semiconducting to metallic conductivity at Tp, the transition occurs within the range 276 K - 288 K which is higher compared with the data reported earlier. Based on the semiconducting model, Ln(R) oc (- E, /K,T) it was observed that the Activation energy, E, value ranges from 100.40 to 118.73 meV. The colossal magnetoresistance effect appears at low temperature and the highest value of CMR effect was observed at temperature approaching Tp. The highest CMR value was observed near the insulatormetal transition. The maximum MR with a value of -68.2% for H = 1.06 T is obtained in the sample prepared at 1 200°C. The specimens of L a 0 . ~ ~ C a 0 ~p~rehpahre0d~ v ia COP method were compared to the specimen prepared by Conventional Powder method (CPM) for samples sintered at 1300°C. XRD spectrum for the samples exhibit orthorhombic distorted and single-phase perovskite structures. The Curie temperature, Tc and the metal-insulator transition temperature, Tp were obtained by ac susceptibility and four- point probe techniques. The results showed that Tc and Tp were 260 K and 276 K respectively for the COP specimen, which is higher than the results obtained by specimen prepared by CPM with Tc and Tp 245 K and 246 K respectively. These results are due to the high chemical homogeneity and high density for the COP specimen as compared to the CPM specimen. The CMR for the (COP) specimen is observed near the insulator- metal transition with the value of - 56% for H = 1.06 T while for the CPM the CMR value of -34%